STUDI KOMPARATIF PELAKSANAAN GLS DI KELAS 4 SD HADI SAKTI DAN SDN 39 CAKRANEGARA - Azahra, Baiq Qory Fatimah; Ida Ermiana; Syaiful Musaddat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the planning, implementation, and evaluation of the implementation of School Literacy Movement (SLM) in SD Hadi Sakti and SDN 39 Cakranegara. The study uses the qualitative approach with descriptive research type. Techniques of collecting data uses interviews, observation, and documentation. Data analysis uses the Miles, Huberman, and Saldana model, namely, data condensation, data display, and drawing conclusions/verification. Validity technique for data uses the the triangulation of source and triangulation of technique. The results showed that: (1) the planning of SLM consist of human resources planning, provision of facilities and infrastructure, funding sources, program planning, and setting the success indicator; (2) the implementation of SLM consist of the activities form of SLM implementation, which are 15 minutes reading program, and provision of reading corners, and the advantages and disadvantages of SLM implementation, includes the advantages which are successfully implemented the 15 minutes reading program, rises the student motivation and reading interest, while the disadvantages is theres no librarian or library officer; (3) the evaluation of SLM implementation, where the implementation of SLM in SD Hadi Sakti and SDN 39 Cakranegara is going well and is in accordance with the plan. This is supported by the supporting factors. Yet in its implementation, there are also found the inhibiting factors. The solution is in the evaluation form as an effort to reduce the inhibiting factors which are done by the evaluation in the class by the teacher directly, monthly evaluation, and evaluation at the end of the semester